The Unit of Analysis in Supply Chain Management Research - MA, JINGJING (2014)
This dissertation will introduce the different unit of analysis in supply chain management research. The dissertation structure more base literature review dissertation. It selects several of academic journal bases on a periodicals journal list focus on supply chain management research. In this dissertation, it choice three issues which are supply chain relationship, sustainable supply chain and supply chain procurement. There were some units of analysis from these issues in order to find which units of analysis are utilizing in supply chain management research recently. The units include specific company case study, research problems and the actually unit they focus on supply chain management research. This dissertation divide into main four parts include background of basic supply chain management issues, supply chain relationship, sustainable supply chain and supply chain procurement. Then, it collects information from current publication for literature review. Next, the finding part a part will introduce the actual finding form these literature review. Finial discussion part will analysis base on separate analysis and all together analysis.